THE USE OF FACEBOOK GROUP DISCUSSION TO IMPROVE READING STRATEGIES: An Action Research - Endang Yuliani Rahayu (Dinamika Bahasa dan Budaya, 2014)
The  rapid development  of technology influence people’s  life  in  many aspects including  the process of teaching and learning  in university, school  etc. Some social medias are popular in society, one of them is Facebook. This social  networking can be used for any purposes Such as  interacting, marketing, publishing, learning etc.  The study aims to prove whether Facebook’s group discussion can be effectively used to improve reading strategies which are normally developed through classroom interaction. It is an action research design involving one group consisting of 37 students randomly sampled out from a population of 198 students. A plan-act-observe-reflect design of the study will be carried out in two cycles. Each cycle involves pretest, treatment and post test. Cycle 1 is undertaken to see if there is a significant difference between the pretest and post test upon treatment. The indicator of success of the treatment is that the post test outscores the pretest. If it does, then  Cycle 2 will be conducted to convince the results. If the two cycles show an increase in the mean scores, it can be claimed that the method is effective. In other words, Facebook’s group discussion can be effectively used to improve reading strategies. Key words:  Facebook group discussion, reading skill